Halal destination images of Japan: a visual content analysis - Sukmayadi, Vidi; Effendi, Ridwan (Penerbit Universiti Kebangsaan Malaysia, 2020)
The scope of the paper is to investigate the construction of visual communication in shaping a Halal destination image in Japan. Even though Japan is located by a significant distance from Islamic countries, halal tourism prominence has become a rapidly growing interest in the country. In fact, in 2016, Japan won the “World’s Best Non-OIC Emerging Halal Destination”, and in 2019, the country was ranked in the top three in the category of non-OIC Muslim-friendly destination for Muslim travellers. The paper attempts to describe the exploration of the images found in Japan’s tourism promotional brochures. The study aimed at interpreting the denotative and connotative messages of the promotional images in the sampled brochures. A visual content analysis was applied to interpret the brochures’ layout and promotional images. The findings of the study imply that distinctive Islamic symbols and Japanese monumental structure are the prominent denotative elements of the brochure. Regarding the connotative elements, the analysis indicates that female Muslim and Halal food become the main Synecdoche in representing Japan’s Halal destination image. It is hoped that the study could give new insights for visual communication and tourism practitioners concerning how images can be constructed to represent the audiences’ interests and experiences.